Sulindac sulfide as a non-immune suppressive γ-secretase modulator to target triple-negative breast cancer - Hossain, Fokhrul; Ucar, Deniz A.; Monticone, Giulia; Ran, Yong; Majumder, Samarpan; Larter, Kristina; Luu, Hanh; Wyczechowska, Dorota; Heidari, Soroor; Xu, Keli; Shanthalingam, Sudarvili; Matossian, Margarite; et al. (Frontiers in Immunology, 2023)
Triple-negative breast cancer (TNBC) comprises a heterogeneous group of clinically aggressive tumors with high risk of recurrence and metastasis. Current pharmacological treatment options remain largely limited to chemotherapy. Despite promising results, the efficacy of immunotherapy and chemo-immunotherapy in TNBC remains limited. There is strong evidence supporting the involvement of Notch signaling in TNBC progression. Expression of Notch1 and its ligand Jagged1 correlate with poor prognosis. Notch inhibitors, including γ-secretase inhibitors (GSIs), are quite effective in preclinical models of TNBC. However, the success of GSIs in clinical trials has been limited by their intestinal toxicity and potential for adverse immunological effects, since Notch plays key roles in T-cell activation, including CD8 T-cells in tumors. Our overarching goal is to replace GSIs with agents that lack their systemic toxicity and ideally, do not affect tumor immunity. We identified sulindac sulfide (SS), the active metabolite of FDA-approved NSAID sulindac, as a potential candidate to replace GSIs. We confirmed that SS, a known γ secretase modulator (GSM), inhibits Notch1 cleavage in TNBC cells. SS significantly inhibited mammosphere growth in all human and murine TNBC models tested. In a transplantable mouse TNBC tumor model (C0321), SS had remarkable single-agent anti-tumor activity and eliminated Notch1 protein expression in tumors. Importantly, SS did not inhibit Notch cleavage in T-cells, and the anti-tumor effects of SS were significantly enhanced when combined with α-PD1 immunotherapy in our TNBC organoids and in vivo. Our data support further investigation of SS for the treatment of TNBC, in conjunction with chemo-or -chemoimmunotherapy. Repurposing an FDA-approved, safe agent for the treatment of TNBC may be a cost-effective, rapidly deployable therapeutic option for a patient population in need of more effective therapies.